Penguatan Ekonomi Lokal Pada Pelaku UMKM Berbasis Digital Di Desa Winduaji Kabupaten Brebes - Achmad Zaki Yamani; Arif Wirawan Muhammad; Muhammad Nur Faiz (Politeknik Negeri Cilacap, 2019)
In the industrial era 4.0, technological knowledge, especially information technology is very important. UMKM are micro-enterprises that should have used the information access for the economic welfare of a region, but vice versa. Current problems with UMKM include lack of capital and knowledge of information technology. Winduaji village is one of the villages with UMKM actors with minimal information technology knowledge. The method of implementation is the method of discussion with the format of Training regarding identifying problems to the use of technology media. This training activity was attended by 56 participants consisting of village officials, UMKM actors, and tourism conscious reservoirs. As a result, all participants showed great interest in using social media marketing continuously.